The Emasculation of Trade Unions and Workers' Drift to Neonationalism in Hungary. Issue 9 (21st October 2021) - Bartha, Eszter; Tóth, András
Abstract: Theoretically, the essay is built on Karl Polanyi's interpretation of disembedding and Chris Hann's application of this model to post-1989 Eastern Europe. The essay sets out to explain why trade unions failed to become a successful countermovement in the Polanyian sense of the word by analysing four sources of power available to unions. We go on to analyse the social and political consequences of this failure, demonstrating through the analysis of life-history interviews how 'lonely fighters' can become rightwing voters and activists, thanks to the rise of a new political culture on the shopfloor.